2011
DOI: 10.1111/j.1442-2050.2011.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

External ultrasonography of the neck does not add diagnostic value to integrated positron emission tomography-computed tomography (PET-CT) scanning in the diagnosis of cervical lymph node metastases in patients with esophageal carcinoma

Abstract: One of the objectives of preoperative imaging in esophageal cancer patients is the detection of cervical lymph node metastases. Traditionally, external ultrasonography of the neck has been combined with computed tomography (CT) in order to improve the detection of cervical metastases. In general, integrated positron emission tomography-computed tomography (PET-CT) has been shown to be superior to CT or PET regarding staging and therefore may limit the role of external ultrasonography of the neck. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Our results are consistent with two articles in the literature that reported no additional value of cervical ultrasonography to integrated 18 F-FDG PET/CT scanning (or standalone PET combined with CT) for detecting cervical lymph node metastases ( n = 170 and n = 136, respectively) [ 14 , 15 ]. One study found an additional value of 4% (3/74) of cervical ultrasonography over standalone PET and CT imaging ( n = 109) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with two articles in the literature that reported no additional value of cervical ultrasonography to integrated 18 F-FDG PET/CT scanning (or standalone PET combined with CT) for detecting cervical lymph node metastases ( n = 170 and n = 136, respectively) [ 14 , 15 ]. One study found an additional value of 4% (3/74) of cervical ultrasonography over standalone PET and CT imaging ( n = 109) [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the use of integrated 18 F-FDG PET/CT is currently highly recommended in initial oesophageal cancer staging [ 13 ]. Owing to the improvement in oesophageal cancer staging by 18 F-FDG PET/CT scanning, it has been suggested that the additional role of cervical ultrasonography for the detection of cervical lymph node metastasis may be limited [ 14 ]. This hypothesis was confirmed in the current cohort of patients in which no additional value of cervical ultrasonography was found to integrated 18 F-FDG PET/CT scanning for the detection of cervical metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since the introduction of PET/CT, the additional role of external ultrasonography to detect cervical lymph node metastases in esophageal cancer staging may be limited. This is suggested by two large series that found no additional value of external ultrasonography over PET/CT with regard to the detection of cervical lymph node metastases . Only one study has shown an additional value of 4% (3/74) of external ultrasonography over CT and PET imaging .…”
Section: Clinical Staging Of Esophageal Carcinomamentioning
confidence: 97%
“…This is suggested by two large series that found no additional value of external ultrasonography over PET/CT with regard to the detection of cervical lymph node metastases. 29,30 Only one study has shown an additional value of 4% (3/74) of external ultrasonography over CT and PET imaging. 31 However, in the latter study, the CT and PET scans were performed separately, which may yield lower diagnostic accuracy compared with integrated PET/CT scanning.…”
Section: Lymph Node Stagingmentioning
confidence: 99%